Constant Enzymatic in situ Production of H2O2 for an Unspecific Peroxygenase by an l–Amino Acid Oxidase - Last, Simon; Heinks, Tobias; Dietz, Niklas; Koopmeiners, Simon; Fischer von Mollard, Gabriele; Weissenborn, Martin J.; Langermann, Jan (Advanced synthesis & catalysis, 2025)
Unspecific Peroxygenases have been the subject of a lot of research in the recent past as they offer opportunities for green hydroxylation reactions using hydrogen peroxide (H2O2) as donor. A striking problem of UPOs is their low stability against their own co‐substrate H2O2. In order to prevent the deactivation, we developed an enzyme cascade with an l‐amino acid oxidase (LAAO) to produce hydrogen peroxide in situ at a constant low concentration, aiming for much higher lifespan and therefore longer working time of the enzyme. This way, we are able to convert a variety of substrates with conversion rates up to 95%.